Training students’ soft skills through group activities - Nguyễn Thị Hiền Hương (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In addition to specialized knowledge, students also need to practise soft skills such as communication skills, presentation skills, discussion skills, problem solving, conflict resolution, listening and sharing ideas, etc. Teamwork is one of the ways to practise these soft skills. With the proper guidance of teachers, we believe that from the first semester of tertiary education, students can have the opportunity to study and train gradually to be well- prepared for life after graduation.